Dose-response of acupuncture on ovulation rates in polycystic ovary syndrome: a meta-analysis and exploratory dose-response analysis - Wei, Jiale; Shen, Zheng; Zhao, ChunYan; Xie, ChunLin; Bai, HongFa; Yin, JiaHui; Wang, Jian (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to evaluate the efficacy of acupuncture in improving ovulation rates in women with polycystic ovary syndrome (PCOS) and to identify optimal dosage parameters, including the number of acupoints, treatment frequency, and session duration, using integrated pairwise meta-analysis, network meta-analysis (NMA), and model-based dose-response modeling.MethodsNine databases were searched up to January 2025, yielding 43 randomized controlled trials (RCTs) involving 4,827 participants that compared acupuncture with sham acupuncture, pharmacotherapy, or conventional therapy control group. Pairwise meta-analysis, NMA, and model-based dose-response modeling were performed.ResultsAcupuncture alone significantly increased ovulation rates compared with sham acupuncture (RR = 1.15, 95% CI: 1.04-1.27) and pharmacotherapy (RR = 1.11, 95% CI: 1.04-1.20). Additionally, acupuncture combined with herbal medicine outperformed pharmacotherapy (RR = 1.27, 95% CI: 1.12-1.43). NMA ranked acupuncture combined with herbal medicine as the most effective intervention (SUCRA = 97.8%). Dose-response modeling identified the following optimal protocols: for acupuncture alone, 30 minutes per session, 29 acupoints, three sessions per week for 24 weeks; and for combined therapy, 19 minutes per session, 26 acupoints, four sessions per week for 24 weeks.ConclusionAcupuncture is an effective non-pharmacological intervention for PCOS-related ovulatory dysfunction, with its efficacy dependent on precise dosing parameters. These findings highlight the need for standardized protocols in future trials to validate dose-response thresholds and to optimize personalized treatment strategies.Systematic review registrationwww.crd.york.ac.uk, identifier PROSPERO (CRD420250651353).